2018
DOI: 10.1186/s12933-017-0655-y
|View full text |Cite
|
Sign up to set email alerts
|

Linagliptin and cardiovascular outcomes in type 2 diabetes after acute coronary syndrome or acute ischemic stroke

Abstract: Background:The cardiovascular safety and efficacy of linagliptin, a dipeptidyl peptidase-4 inhibitor, in patients with type 2 diabetes mellitus (T2DM) after acute coronary syndrome (ACS) or acute ischemic stroke (AIS) are unclear. The aim of our real-world cohort study was to evaluate the cardiovascular outcomes of linagliptin in patients with T2DM after ACS or AIS.Methods: An open observational noncrossover retrospective cohort study was conducted between June 1, 2012 and December 31, 2013 utilizing Taiwan Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Another study based on the Taiwan National Health Insurance Research Database evaluated the association between linagliptin and major CV events in a population of 1203 patients with T2D after an episode of acute coronary syndrome or ischaemic stroke. Compared with patients who did not receive any incretin‐based therapy, linagliptin users had a similar risk of major CV events (HR 1.06, 95% CI 0.66‐1.68) . These results complement our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Another study based on the Taiwan National Health Insurance Research Database evaluated the association between linagliptin and major CV events in a population of 1203 patients with T2D after an episode of acute coronary syndrome or ischaemic stroke. Compared with patients who did not receive any incretin‐based therapy, linagliptin users had a similar risk of major CV events (HR 1.06, 95% CI 0.66‐1.68) . These results complement our findings.…”
Section: Discussionsupporting
confidence: 86%
“…In the TIMI 53 study, the DPP‐4 inhibitor saxagliptin did not reduce the incidence of NAF (0.93% vs 0.94%) . Also, in a smaller study, the outcomes of 401 participants who received linagliptin were compared with those of matched control participants who did not receive incretin‐based therapies, and the use of linagliptin was not associated with an increase in the development of NAF . Therefore, it is probable that DPP‐4 inhibitors neither increase nor decrease the incidence of NAF.…”
Section: Newer Diabetes Therapies and The Risk Of Atrial Fibrillationmentioning
confidence: 99%
“…78 Also, in a smaller study, the outcomes of 401 participants who received linagliptin were compared with those of matched control participants who did not receive incretin-based therapies, and the use of linagliptin was not associated with an increase in the development of NAF. 79 Therefore, it is probable that DPP-4 inhibitors neither increase nor decrease the incidence of NAF. Based on the data described above, we can conclude that, among the drugs that lower insulin resistance, only pioglitazone and metformin, but not rosiglitazone, reduce the incidence of NAF.…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…Simultaneously, another research group in Taiwan from which they identified 16 017 patients in the cohort of DPP4 inhibitor users and 74 863 patients in the cohort of DPP4 inhibitor nonusers and reported that DPP4 inhibitor therapy is associated with a decreased risk of developing NAF . However, another study identified 401 linagliptin users who had acute coronary syndrome or acute ischaemic stroke and 802 controls (matched with patient characteristics, baseline comorbidities, medication prescribed 90 days since indexed hospitalization and index year and month by propensity score) . They concluded that the risk of developing NAF was neutral between linagliptin users and nonusers.…”
Section: Antihyperglycaemic Drugs Use and New‐onset Atrial Fibrillatimentioning
confidence: 99%
“…28 However, another study identified 401 linagliptin users who had acute coronary syndrome or acute ischaemic stroke and 802 controls (matched with patient characteristics, baseline comorbidities, medication prescribed 90 days since indexed hospitalization and index year and month by propensity score). 29 They concluded that the risk of developing NAF was neutral between linagliptin users and nonusers. Thus, it is possible that DPP4 inhibitors have not been shown to increase the risk of developing NAF.…”
Section: Drugs Use and New-onset Atrial Fibrillation In Elderly Patiementioning
confidence: 99%